Early Network-based Action Against Violent Behaviors to Leverage victim Empowerment: Results from an action-research plan - Ranghetti, Francesca; Miragoli, Sarah; Giulini, Paolo; Rho, Benedetta; Emiletti, Laura; Contino, Marina; Tassone, Elvira; Battaglia, Umberto; Corbucci, Elisabetta; Merli, Silvia; Murru, Susanna; Milani, Luca (Ricerche di Psicologia - Open Access, 2024)
The ENABLE project, which aims to implement the ZEUS protocol at the national level, aims to activate specific interventions to prevent violence against women by going directly to individuals who have been admonished for domestic violence or stalking, thus implementing a system of protection towards victims. A second objective concerns the implementation of a training intervention aimed at project workers and law enforcement officers. The topic of gender-based violence, identification and management of situations at risk of escalation through the construction of shared operational practices was the subject of the training. Following the trainings, a quantitative survey was administered to law enforcement officers (both training participants and non-trainees) to assess their knowledge of the instrument of warning, referral to treatment and specific forms of gender-based victimization, use of referrals to treatment, and knowledge of gender-specific forms of victimization. The results showed significant differences between participants versus non-participants to ENABLE training, with respect to intervention effectiveness, awareness and knowledge related to the training. With regard to the admonished and petitioning parties, two different surveys were administered aimed at investigate, at the end of intake, clinical and individual adjustment variables (in terms of depression and posttraumatic symptoms, coping strategies, risk of victimization, and adverse childhood experiences). The results showed significant differences between the two groups (admonished versus instant parties), particularly with regard to the depressive and post-traumatic risk variables, with the instant parties being more likely to be exposed to this condition than the admonished.